A Craniofacial Morphology Study Of Patients With Obstructive Sleep Apnea [RC737.5. M697 2005 f rb]. - Mohammed, Dr. Osama Bahaa (2005)

(untitled)
Obstructive sleep apnea (OSA) is defined as a repetitive cessations of breathing (apneas) lasting for at least 10 seconds or more for each event during sleep. The respiratory muscles attempt to inspire, but blockages in the upper airway prevent air from reaching the lungs.